2021
DOI: 10.1002/bbb.2297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of herbaceous feedstock supply for locating biorefineries in the Piedmont, USA

Abstract: The push for renewable energy sources has local government agencies striving to optimize their limited resources. Various energy sources are often explored depending on the region – for example, wind, solar, geothermal, and bioenergy. The Piedmont region of the USA has the potential to be a significant player in the production of biomass to supply a biorefinery. However, before local agencies and private biorefineries can invest in such an endeavor, the potential feedstock supply must be quantified. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…The methodology described here for the central control model could easily be applied to other herbaceous biomass production zones. Resop and Cundiff [4] identified 34 potential multicounty production zones in the Piedmont region (spanning Virginia to Alabama) with estimated production ranging from 50,000 to 360,000 Mg, similar in size to the area defined for this study. Future research should apply the central control model to these other potential production zones and determine whether the optimal number of load-out operations varies between zones.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The methodology described here for the central control model could easily be applied to other herbaceous biomass production zones. Resop and Cundiff [4] identified 34 potential multicounty production zones in the Piedmont region (spanning Virginia to Alabama) with estimated production ranging from 50,000 to 360,000 Mg, similar in size to the area defined for this study. Future research should apply the central control model to these other potential production zones and determine whether the optimal number of load-out operations varies between zones.…”
Section: Discussionmentioning
confidence: 89%
“…The US Department of Energy (DOE) has set a goal of replacing at least 30% of the country's current petroleum consumption with biomass by 2030 [1]. Towards this endeavor, many studies have demonstrated the potential for different regions of the country to grow sustainable biomass [2][3][4]. These studies generally organize areas into production zones, defined as multicounty regions that have the potential to supply a biorefinery with herbaceous feedstock [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depot sites were chosen from 34 potential biorefinery locations, defined as multi‐county production zones, in the Piedmont province 5 . The study area was chosen to encompass a region that has already undergone extensive research into the logistics for delivery of herbaceous feedstock from SSLs to a potential biorefinery centered in Gretna, Virginia 11,16 .…”
Section: Methodsmentioning
confidence: 99%
“…However, this region has been shown to have the natural resources available, such as the proper climate, soils, and land use, to potentially produce a significant amount of the country's demand for biofuel 4 . Resop and Cundiff 5 previously identified 34 multi‐county production zones in the Piedmont province with potential annual production of switchgrass for biofuel ranging from 50 000 Mg to 360 000 Mg per zone. Switchgrass ( Panicum virgatum L.), a perennial, warm‐season grass, as the potential biofuel feedstock was selected again for this study due to a long history of research that has shown it to be a flexible and resilient crop that can be grown under many diverse climates 6 …”
Section: Introductionmentioning
confidence: 99%